Transformational Leadership, Knowledge Sharing, and Health Policy: A Qualitative Study in Organizational Contexts - Suprapto Suprapto; Nawir Rahman (Edukasi Ilmiah Indonesia, 2026)
Introduction: Introduction: Knowledge sharing is essential for organizational learning and public sector performance, yet hierarchical bureaucratic cultures often inhibit open knowledge exchange. Transformational leadership has been proposed as a critical social enabler, but contextual qualitative evidence remains limited, particularly in Indonesian public sector organizations. Methods: This study employed a qualitative phenomenological design involving 20–25 participants from Indonesian public institutions. Data were collected through semi-structured in-depth interviews and analyzed using thematic analysis. Trustworthiness was ensured through member checking, peer debriefing, and audit trails. Results: The findings reveal that transformational leadership fosters sustainable knowledge-sharing practices through sequential socio-psychological mechanisms. Psychological safety emerged as the foundational condition, followed by the development of interpersonal trust and intrinsic motivation. These mechanisms institutionalized reciprocal norms that normalized voluntary knowledge exchange. However, hierarchical structures and power distance moderated the strength of these effects. Conclusion: Transformational leadership enhances knowledge sharing indirectly by shaping relational climate rather than through formal authority. Leadership development integrated with cultural reform initiatives represents a strategic intervention to strengthen organizational learning and performance within the public sector and public health systems